1989
DOI: 10.1042/bj2580409
|View full text |Cite
|
Sign up to set email alerts
|

Capacitative calcium entry in parotid acinar cells

Abstract: The intracellular Ca2+ indicator, fura-2, was used to monitor changes in cytosolic [Ca2+] in parotid acinar cells. When parotid cells were incubated in a medium containing low [Ca2+], and [Ca2+] was restored to the physiological range, there was a small increase in cytosolic [Ca2+]. If, however, the cells were first activated by a muscarinic agonist, and receptor activation was terminated before the addition of Ca2+ by the addition of a pharmacological excess of the muscarinic-receptor antagonist atropine, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
80
1

Year Published

1992
1992
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 217 publications
(90 citation statements)
references
References 18 publications
9
80
1
Order By: Relevance
“…Therefore, calmodulin antagonists have been proposed as useful tools for identifying the type of NO synthase involved in relaxation (Schini & Vanhoutte, 1992). In this respect, in the present experiments, it was found that the calmodulin inhibitors selectively abolished endothe-5 4 lium-dependent relaxation and increase in cyclic GMP formation induced by CPA as well as by ACh, without affecting the endothelium-independent nitroprusside-induced respon- Ca-free (Merritt & Rink, 1987;Pandol et al, 1987;Takemura & Putney, 1989;Kwan et al, 1990;Mertz et al, 1990; :opiazonic acid 1990; Demaurex et al, 1992;Low et al, 1992 brane Ca2"' channels subsequent to depletion by CPA of stored Ca2" may activate NO synthase.…”
Section: Discussionmentioning
confidence: 88%
“…Therefore, calmodulin antagonists have been proposed as useful tools for identifying the type of NO synthase involved in relaxation (Schini & Vanhoutte, 1992). In this respect, in the present experiments, it was found that the calmodulin inhibitors selectively abolished endothe-5 4 lium-dependent relaxation and increase in cyclic GMP formation induced by CPA as well as by ACh, without affecting the endothelium-independent nitroprusside-induced respon- Ca-free (Merritt & Rink, 1987;Pandol et al, 1987;Takemura & Putney, 1989;Kwan et al, 1990;Mertz et al, 1990; :opiazonic acid 1990; Demaurex et al, 1992;Low et al, 1992 brane Ca2"' channels subsequent to depletion by CPA of stored Ca2" may activate NO synthase.…”
Section: Discussionmentioning
confidence: 88%
“…It is probable that localized SR calcium depletion could limit agonist-elicited SR quantal release. Calcium influx can occur through a variety of mechanisms, including voltage-and receptor-operated membrane channels, and store-operated calcium entry (SOCE) (1,6,(26)(27)(28)(29). Calcium influx by SOCE is triggered by depletion of the intracellular stores and may be influenced by the second messenger systems eliciting calcium release (30).…”
Section: Cyclic Adp-ribose As An Endogenous Ligand For the Ryanodine mentioning
confidence: 99%
“…In the last case, store-operated Ca 2ϩ entry (SOCE) is triggered by depletion of SR Ca 2ϩ stores (6,41,42,49,55,56). We and others have shown that different transient receptor potential channel (TRPC) isoforms are expressed in ASM (6,58).…”
mentioning
confidence: 99%